2010
DOI: 10.4028/www.scientific.net/amr.152-153.945
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Phosphorus Adsorption from Aqueous Solutions on Modified Activated Alumina

Abstract: In the study, activated alumina was modified by calcium chloride, and after modification the phosphorus removal from aqueous solution increased by 13% or so. Then the activated alumina with and without treatment were subjected to characterization by the methods of the BET and SEM, and the adsorption characteristics of modified activated alumina were further studied at different contact time, pH values, adsorbent dosage levels and initial phosphorus concentration. Moreover, the equilibrium adsorption data for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Among them, adsorption is usually regarded as a simple and convenient method. Further research has been done in recent years to search for adsorbent materials suitable for industrial production with high adsorption efficiency [6][7][8][9][10][11][12]. Studies have shown that phosphorus in eutrophic water exists as free phosphate, and a large amount of metal oxide/hydroxide has been used in phosphorus removal because of its specific affinity for phosphate including hydrous ferric oxide [13], magnetite [14], hydrous manganese oxide [15], aluminum hydroxide gel [16], lanthanum hydroxide [17], cerium oxide [18], titanium dioxide [19], hydrous niobium oxide [20], and zirconium oxide/hydroxide [21,22], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, adsorption is usually regarded as a simple and convenient method. Further research has been done in recent years to search for adsorbent materials suitable for industrial production with high adsorption efficiency [6][7][8][9][10][11][12]. Studies have shown that phosphorus in eutrophic water exists as free phosphate, and a large amount of metal oxide/hydroxide has been used in phosphorus removal because of its specific affinity for phosphate including hydrous ferric oxide [13], magnetite [14], hydrous manganese oxide [15], aluminum hydroxide gel [16], lanthanum hydroxide [17], cerium oxide [18], titanium dioxide [19], hydrous niobium oxide [20], and zirconium oxide/hydroxide [21,22], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Alumina adsorbent is a cheap material with a broad application foreground in phosphorus removal. However, previous studies have shown that the adsorption capacity of the alumina adsorbent is not high enough because of the low specific surface area [23][24][25][26][27][28]. At present, the industrialized methods for producing alumina include aluminum alcohol hydrolysis, sodium metaaluminate-carbon dioxide method and neutralization method.…”
Section: Introductionmentioning
confidence: 99%
“…In a solution containing negatively charged phosphorus ions, electrostatic attraction between the positively charged pumice and the negatively charged phosphorus ions lead to increase in removal efficiency. Natural pumice has some impurity and low sorption capacity and it is also negatively charged [52,53]. Therefore, the objective of adsorbent modification using acid is an improvement of positive surface charges of adsorbent and its adsorption capacity.…”
Section: Effect Of Phmentioning
confidence: 99%
“…The basic features of Langmuir isotherm can be described by a constant known as equilibrium parameter R L [53,58,59]: Table 6 Specifications of the kinetics models investigated in this study…”
Section: Adsorption Isothermmentioning
confidence: 99%